Pengembangan e-Modul Pembelahan Sel Bagi Siswa Kelas XII MIA SMA Negeri 1 Nunukan - Ismiati Ismiati; Yusminah Hala; Muhiddin Palennari (UNM Journal of Biological Education, 2022)
This study aims to produce a product in a form of teaching material of a biology e-module which is expected to assist teachers and students learn about cell division. The method used is research and development by adapting the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The stages of analysis are conducted by analyzing the curriculum used, the students’ characteristics, and the use of current technology. Followed by design and development, namely the manufacture of e-module, product validation and revision. The next stage is implementation with a trial of applying the e-biology module to students. The last stage is evaluation, namely analyzing the results of the final revision. The research instruments used were instrument validation sheet, teacher’s response questionnaires, students’ questionnaires, and learning outcomes test. The sample of the study were students of grade XII MIA at SMAN 1 Nunukan. Based on the results of data analysis, it shows that 1) the Biology e[1]module learning media on cell division material meets the valid criteria with a mean score of 4.5 (valid); 2) the Biology e-module learning media on cell division material meets the practical criteria based on the result of the teachers’ responses by 83.48% (very positive) and the result of the students’ responses is 85.63% (positive); 3) the Biology e-module learning media on cell division material meets the effective criteria with the percentage of learning outcomes completeness of 88.57% (very good). Based on the results of the study, it can be concluded that the Biology e-module learning media on cell division material has met valid, practical, and effective criteria.